WEBVTT
00:00:01.160 --> 00:00:05.490
In this video, weβll learn how to find the derivative of exponential functions.
00:00:06.260 --> 00:00:18.740
Weβll begin by stating the formula for the derivative of an exponential function in the form π of π₯ equals π to the π₯ and π to the ππ₯, before applying this formula to examples of increasing complexity.
00:00:19.320 --> 00:00:26.650
Weβll also see how we can use the laws of exponentials and logarithms to find the derivative of general exponential functions.
00:00:28.190 --> 00:00:38.250
Remember, an exponential function is one of the form π of π₯ equals ππ to the power of π₯, where π and π are constants and π is greater than zero.
00:00:39.110 --> 00:00:49.900
Weβre actually first going to consider the derivative of a special form of this, the exponential function π of π₯ equals π to the π₯ and π of π₯ equals π to the ππ₯.
00:00:50.210 --> 00:00:55.470
Now a common misconception is to think that we can apply the power rule to these exponential functions.
00:00:55.860 --> 00:01:01.610
In fact, the power rule only applies when the exponent is fixed and the bases are variable.
00:01:01.980 --> 00:01:06.690
In the exponential functions, the base is fixed and the exponent is the variable.
00:01:06.990 --> 00:01:19.110
So weβll instead need to use a separate formula for the derivative of an exponential function, though the derivation of this formula is achievable if you know how to differentiate the inverse of π to the π₯ or ln π₯.
00:01:19.490 --> 00:01:22.360
And it can also be achieved through first principles.
00:01:22.490 --> 00:01:25.660
But it is outside of the constraints of this video to look at all of these.
00:01:25.860 --> 00:01:31.640
So instead, weβll state the formula for the derivative of π to the power of π₯ and π to the power of ππ₯.
00:01:32.270 --> 00:01:37.180
The derivative of π to the power of π₯ with respect to π₯ is π to the power of π₯.
00:01:37.550 --> 00:01:39.340
And this formula can be generalized.
00:01:39.370 --> 00:01:45.900
And we can say that the derivative of π to the power of ππ₯ with respect to π₯ is ππ to the ππ₯.
00:01:46.170 --> 00:01:49.980
Now, the function π of π₯ equals π to the π₯ is incredibly unusual.
00:01:50.370 --> 00:01:54.190
Its derivative is the same as the original function.
00:01:54.620 --> 00:02:03.320
Geometrically, this means that, for every value of π₯, the slope or the gradient of the tangent to the curve at that point is equal to the π¦-value.
00:02:03.940 --> 00:02:12.120
For example, when π₯ is equal to two, π¦ is equal to π to the power of two, which is approximately 7.39.
00:02:12.680 --> 00:02:22.860
Since the derivative of π to the power of π₯ is π to the power of π₯, this means that the gradient of the tangent to the curve at that point is also 7.39.
00:02:24.000 --> 00:02:27.290
Letβs have a look at an example of the application of these formulae.
00:02:28.410 --> 00:02:35.010
If π of π₯ is equal to negative five π to the negative nine π₯, find π dash of π₯.
00:02:35.130 --> 00:02:37.270
Find the derivative of the function.
00:02:38.010 --> 00:02:42.290
Remember, the derivative of π to the power of π₯ is π to the power of π₯.
00:02:42.470 --> 00:02:46.850
And the derivative of π to the power of ππ₯ is ππ to the ππ₯.
00:02:47.260 --> 00:02:51.400
Now, our function is some multiple of π to the ππ₯.
00:02:51.590 --> 00:02:56.200
Itβs negative five times π to the ππ₯, where π is equal to negative nine.
00:02:56.950 --> 00:03:06.390
Now, we know that the constant factor rule allows us to take constants outside a derivative and concentrate on differentiating the function of π₯ itself.
00:03:06.800 --> 00:03:15.430
So this means we can say that the derivative of the function of π₯ is equal to negative five times the derivative of π to the negative nine π₯.
00:03:15.800 --> 00:03:22.600
And we know that the derivative of π to the negative nine π₯ is negative nine times π to the negative nine π₯.
00:03:23.250 --> 00:03:32.820
And since negative five multiplied by negative nine is 45, we can say that the derivative of our function is 45π to the negative nine π₯.
00:03:33.990 --> 00:03:35.670
Letβs consider another example.
00:03:36.570 --> 00:03:42.730
Find dπ¦ by dπ₯ if five π¦π to the two π₯ equals seven π to the five.
00:03:43.460 --> 00:03:46.300
Now, at first glance, this does look a little complicated.
00:03:46.700 --> 00:03:51.480
However, we can clearly see that we can rearrange the equation to make π¦ the subject.
00:03:51.930 --> 00:03:56.850
Weβre going to divide both sides of the equation by five π to the two π₯.
00:03:57.370 --> 00:03:59.760
On the left-hand side, that leaves us simply with π¦.
00:04:00.320 --> 00:04:05.960
And on the right-hand side, we have seven π to the power of five over five π to the two π₯.
00:04:06.260 --> 00:04:11.550
Now, actually, one over π to the power of two π₯ is equal to π to the negative two π₯.
00:04:11.880 --> 00:04:13.470
So we can rewrite our equation.
00:04:13.470 --> 00:04:19.930
And we say that π¦ is equal to seven π to the power of five over five times π to the negative two π₯.
00:04:20.220 --> 00:04:24.090
Notice that seven π to the five over five is just a constant.
00:04:24.380 --> 00:04:30.080
So we can differentiate this using the general formula for the derivative of the exponential function.
00:04:30.350 --> 00:04:34.750
The derivative of π to the ππ₯ with respect to π₯ is ππ to the ππ₯.
00:04:35.100 --> 00:04:43.840
And of course, remembering that the constant factor rule allows us to take constants outside a derivative and concentrate on differentiating the function of π₯ itself.
00:04:44.310 --> 00:04:54.060
In other words, dπ¦ by dπ₯ is equal to seven π to the power of five over five times the derivative of π to the negative two π₯ with respect to π₯.
00:04:54.370 --> 00:05:00.890
And the derivative of π to the negative two π₯ with respect to π₯ is negative two π to the negative two π₯.
00:05:01.310 --> 00:05:08.900
This means dπ¦ by dπ₯ is negative two times seven π to the power of five over five times π to the negative two π₯.
00:05:09.280 --> 00:05:18.650
Notice that the derivative can actually be expressed in terms of π¦ since we said that π¦ was equal to seven π to the power of five over five times π to the negative two π₯.
00:05:19.190 --> 00:05:23.700
And we can therefore say that dπ¦ by dπ₯ is equal to negative two π¦.
00:05:25.260 --> 00:05:30.400
Next, we consider a slightly more complex example, in which weβll need to apply other rules for differentiation.
00:05:31.640 --> 00:05:38.800
Find the derivative of the function π of π§ equals negative three π to the four π§ over four π§ plus one.
00:05:39.650 --> 00:05:43.780
Here we have a function of a function or a composite function.
00:05:44.290 --> 00:05:47.270
This tells us weβre going to need to apply the chain rule.
00:05:47.930 --> 00:05:57.980
This says that the derivative of π of π of π₯ is equal to the derivative of π of π of π₯ multiplied by the derivative of π of π₯.
00:05:58.520 --> 00:06:08.630
Alternatively, we can say that if π¦ is equal to this composite function, π of π of π₯, then if we let π’ be equal to π of π₯, then π¦ is equal to π of π’.
00:06:09.140 --> 00:06:20.250
And this means we can say that the derivative of π¦ with respect to π₯ is equal to the derivative of π¦ with respect to π’ multiplied by the derivative of π’ with respect to π₯.
00:06:20.630 --> 00:06:29.320
In this example, we say that π¦ is equal to negative three times π to the power of π’, where π’ is equal to four π§ over four π§ plus one.
00:06:29.880 --> 00:06:34.140
And since weβre going to be differentiating with respect to π§, we alter the formula slightly.
00:06:34.400 --> 00:06:39.050
And we say that dπ¦ by dπ§ is equal to dπ¦ by dπ’ times dπ’ by dπ§.
00:06:39.440 --> 00:06:43.650
So weβre going to need to work out dπ¦ by dπ’ and dπ’ by dπ§.
00:06:44.040 --> 00:06:47.450
dπ¦ by dπ’ is a fairly easy one to differentiate.
00:06:47.670 --> 00:06:51.250
We know that the derivative of π to the power of π’ is π to the power of π’.
00:06:51.810 --> 00:06:56.800
So the derivative of negative three π to the power of π’ is negative three π to the power of π’.
00:06:57.200 --> 00:07:04.570
And then, we can replace π’ with four π§ over four π§ plus one to get negative three π to the four π§ over four π§ plus one.
00:07:05.100 --> 00:07:08.980
But what about the derivative of four π§ over four π§ plus one?
00:07:10.050 --> 00:07:12.360
Well, here, we need to use the quotient rule.
00:07:12.740 --> 00:07:24.000
This says that the derivative of π of π₯ over π of π₯ is equal to the function π of π₯ times the derivative of π of π₯ minus the function π of π₯ times the derivative of π of π₯.
00:07:24.350 --> 00:07:26.670
And thatβs all over π of π₯ squared.
00:07:27.220 --> 00:07:30.660
We change π of π₯ to π of π§ and π of π₯ to π of π§.
00:07:31.240 --> 00:07:34.840
Then, the derivative of the numerator of our fraction is four.
00:07:35.350 --> 00:07:38.540
And the derivative of the denominator of our fraction is also four.
00:07:38.870 --> 00:07:44.920
So the equivalent to π of π§ times the derivative of π of π§ is four π§ plus one times four.
00:07:45.350 --> 00:07:50.590
And the equivalent to π of π§ times the derivative of π of π§ is four π§ times four.
00:07:51.000 --> 00:07:53.630
And thatβs all over the denominator squared.
00:07:53.630 --> 00:07:55.360
Thatβs four π§ plus one squared.
00:07:55.790 --> 00:08:00.790
Now, distributing the parentheses and we simply end up with four on the numerator of this fraction.
00:08:01.240 --> 00:08:05.730
So dπ’ by dπ§ is equal to four over four π§ plus one squared.
00:08:06.290 --> 00:08:09.660
Letβs now substitute everything we have into the formula for the chain rule.
00:08:10.090 --> 00:08:20.060
dπ¦ by dπ’ times dπ’ by dπ§ is negative three π to the four π§ over four π§ plus one times four over four π§ plus one squared.
00:08:20.570 --> 00:08:30.130
And if we simplify, we see that the derivative of our function is negative 12π to the four π§ over four π§ plus one all over four π§ plus one squared.
00:08:31.380 --> 00:08:38.640
Our next example will lead us into a definition for the derivative of an exponential equation in the form ππ to the power of π₯.
00:08:39.370 --> 00:08:45.070
If π¦ is equal to negative three times two to the power of π₯, determine dπ¦ by dπ₯.
00:08:45.440 --> 00:08:56.600
To answer this question, weβll first recall the fact that the constant factor rule allows us to take constants outside of a derivative and concentrate on differentiating the function of π₯ itself.
00:08:56.880 --> 00:09:04.500
We can therefore say that dπ¦ by dπ₯ is equal to negative three times the derivative of two to the power of π₯ with respect to π₯.
00:09:04.960 --> 00:09:07.670
But how do we differentiate two to the power of π₯?
00:09:08.010 --> 00:09:11.410
Well, weβre going to use the laws of logarithms and exponentials.
00:09:11.540 --> 00:09:15.940
We start by saying that two is the same as π to the power of ln two.
00:09:16.380 --> 00:09:20.520
And remember, this is true because π and ln are inverse functions of one another.
00:09:21.170 --> 00:09:31.800
Next, we raise both sides of this equation to the power of π₯ and use the laws of exponents to say that two to the power of π₯ is equal to π to the power of ln two times π₯.
00:09:32.160 --> 00:09:34.600
Well, ln two is just a constant.
00:09:35.220 --> 00:09:40.370
So we use the fact that the derivative of π to the ππ₯ is ππ to the ππ₯.
00:09:40.540 --> 00:09:47.160
And we can say that the derivative of two to the power of π₯ is ln two times π to the ln two π₯.
00:09:47.620 --> 00:09:54.530
This means that dπ¦ by dπ₯ is equal to negative three multiplied by ln two times π to the ln two π₯.
00:09:54.960 --> 00:09:59.740
Now, remember, we actually defined two to the power of π₯ to be π to the ln two π₯.
00:09:59.900 --> 00:10:03.410
So we replace π to the ln two π₯ with two to the power of π₯.
00:10:03.600 --> 00:10:09.700
And we see that dπ¦ by dπ₯ in this case is negative three times ln two times two to the power of π₯.
00:10:11.540 --> 00:10:14.830
Now, we can generalize the result from the previous example.
00:10:15.050 --> 00:10:22.430
And we can say that the derivative of an exponential function of the form π to the power of π₯ is ln π times π to the power of π₯.
00:10:22.560 --> 00:10:24.040
And we can generalize that somewhat.
00:10:24.040 --> 00:10:32.050
And we say that the derivative of π to the power of ππ₯ is equal to π times ln of π times π to the power of ππ₯.
00:10:32.200 --> 00:10:40.480
And whilst itβs very useful to learn this formula by heart, itβs also important that youβre able to follow the process that we took before for finding them.
00:10:41.020 --> 00:10:43.340
Letβs look at the application of these formulae.
00:10:44.080 --> 00:10:51.780
Find the first derivative of the function π¦ equals seven to the power of negative nine π₯ minus eight all to the power of negative two.
00:10:52.510 --> 00:10:57.770
To find the derivative of this function, weβll first want to see if thereβs a way in which we can simplify it somewhat.
00:10:58.120 --> 00:11:00.980
In fact, we can use the laws of exponents to do so.
00:11:01.340 --> 00:11:06.770
Remember, π to the power of π to the power of π is equal to π to the power of π times π.
00:11:07.220 --> 00:11:16.780
So we can say that seven to the power of negative nine π₯ minus eight all to the power of negative two is the same as seven to the power of 18π₯ plus 16.
00:11:17.350 --> 00:11:19.330
We then use another law of exponents.
00:11:19.480 --> 00:11:24.930
This time, π to the power of π times π to the power of π is the same as π to the power of π plus π.
00:11:25.370 --> 00:11:30.800
So π¦ must be equal to seven to the power of 18π₯ times seven to the power of 16.
00:11:31.190 --> 00:11:33.620
Now, seven to the power of 16 is a constant.
00:11:33.970 --> 00:11:45.070
So we can say that the first derivative of our function dπ¦ by dπ₯ is equal to seven to the power of 16 times the derivative of seven to the power of 18π₯ with respect to π₯.
00:11:45.420 --> 00:11:55.690
And here, we use the fact that the derivative of π to the power of ππ₯ with respect to π₯ is equal to π times ln of π times π to the power of ππ₯.
00:11:56.000 --> 00:12:04.260
And this means the derivative of seven to the power of 18π₯ is 18 times ln of seven times seven to the power of 18π₯.
00:12:04.540 --> 00:12:10.290
Now, once again, weβll use the fact that π to the power of π times π to the power of π is the same as π to the power of π plus π.
00:12:10.710 --> 00:12:17.250
And we can rewrite seven to the power of 16 times seven to the power of 18π₯ as seven to the power of 18π₯ plus 16.
00:12:17.720 --> 00:12:25.530
And this means the first derivative of our function is 18 times ln seven times seven to the power of 18π₯ plus 16.
00:12:26.880 --> 00:12:31.860
In our final example, weβll look at a worded problem involving the derivatives of exponentials.
00:12:32.830 --> 00:12:37.690
The radioactive decay of Radon-222 is modeled by the following formula.
00:12:38.060 --> 00:12:49.360
π of π‘ equals π nought times a half to the power of π‘ over π‘ half, where π of π‘ is the remaining quantity, in grams, of Radon-222 which has not decayed after π‘ days.
00:12:49.810 --> 00:12:52.560
π nought is the initial quantity of Radon-222.
00:12:52.910 --> 00:12:54.740
And π‘ half is its half-life.
00:12:55.410 --> 00:12:59.480
A particular sample initially contained 10 grams of Radon-222.
00:12:59.950 --> 00:13:08.010
Given that the half-life of Radon-222 is 3.8215 days, find the rate of decay of the sample 10 days later.
00:13:08.320 --> 00:13:10.400
Give your answer to three significant figures.
00:13:10.940 --> 00:13:17.450
Remember, rate of change or, here rate of decay, will always correspond to the gradient function or the derivative.
00:13:17.770 --> 00:13:25.420
To answer this question then, weβre going to need to differentiate the function π nought times a half to the power of π‘ over π‘ half with respect to π‘.
00:13:25.830 --> 00:13:27.400
Now, this may look a little tricky.
00:13:27.510 --> 00:13:31.780
However, π nought is a constant as is π‘ half.
00:13:32.010 --> 00:13:39.400
And we use the fact that the derivative of π to the ππ₯ is π times ln π times π to the ππ₯.
00:13:39.730 --> 00:13:56.810
And we can say that the derivative of π with respect to π‘ is equal to π nought times one over π‘ half, since in our equation thatβs the equivalent of π, times ln of a half, since in our equation π is a half, times a half to the power of π‘ over π‘ half.
00:13:57.100 --> 00:14:02.510
Now, we rewrite ln of a half and say that thatβs the same as ln of two to the power of negative one.
00:14:02.930 --> 00:14:04.420
And we use the laws of logarithms.
00:14:04.420 --> 00:14:10.150
And we see that ln of a half is the same as negative one times ln two or just negative ln two.
00:14:10.730 --> 00:14:13.060
And so we can rewrite our expression a little.
00:14:13.390 --> 00:14:20.910
Now, since a particular sample initially contained 10 grams of Radon-222, we can say that π nought must be equal to 10.
00:14:21.330 --> 00:14:24.920
We know that π‘ half is equal to 3.8215.
00:14:25.220 --> 00:14:28.690
And weβre looking to find the rate of decay when π‘ is equal to 10.
00:14:29.040 --> 00:14:32.270
So weβll substitute all of these into our equation for the derivative.
00:14:32.580 --> 00:14:41.530
And we get 10 over 3.8215 times negative ln two times a half to the power of 10 over 3.8215.
00:14:42.020 --> 00:14:46.590
And that gives us a value of negative 0.2957.
00:14:47.060 --> 00:14:49.790
But what does this actually mean with respect to our question?
00:14:50.200 --> 00:14:55.850
Well, correct to three significant figures, the rate of change is equal to negative 0.296.
00:14:56.060 --> 00:15:02.570
Now, since this is negative, it means the sample is decaying at a rate of 0.296 grams per day.
00:15:04.370 --> 00:15:08.740
In this video, weβve seen that the derivative of π to the power of π₯ is π to the power of π₯.
00:15:09.490 --> 00:15:11.310
And weβve seen that this can be generalized.
00:15:11.310 --> 00:15:16.910
And we can say that the derivative of π to the power of ππ₯ is equal to π times π to the power of ππ₯.
00:15:17.410 --> 00:15:24.060
We also saw that we can differentiate π to the power of π₯ with respect to π₯ to get ln π times π to the power of π₯.
00:15:24.280 --> 00:15:31.780
And we generalize that to say that the derivative of π to the power of ππ₯ is equal to π times ln π times π to the power of ππ₯.
00:15:32.060 --> 00:15:38.990
We also saw that it can be useful to simplify or manipulate expressions using the rules of exponents before differentiating.
00:15:39.400 --> 00:15:45.100
And we said that itβs important not to confuse the power rule and the rule for differentiating exponential functions.